Comparison of effects of pitavastatin and atorvastatin on glucose metabolism in type 2 diabetic patients with hypercholesterolemia. Issue 3 (13th February 2013) - Mita, Tomoya; Nakayama, Shiho; Abe, Hiroko; Gosho, Masahiko; Iida, Hitoshi; Hirose, Takahisa; Kawamori, Ryuzo; Watada, Hirotaka
Abstract Aims/Introduction The distinct effects of different statins on glycemic control have not been fully evaluated. In this open‐label, prospective, cross‐over clinical trial, we compared the effects of pitavastatin and atorvastatin on glycemic control in type 2 diabetic patients with hypercholesterolemia. Materials and Methods A total of 28 Japanese type 2 diabetics with hypercholesterolemia treated with rosuvastatin (2.5 mg/day) for at least 8 weeks were recruited to this quasi‐randomized cross‐over study. At study entry, the patients assigned to sequence 1 received pitavastatin (2 mg/day) for 12 weeks in period 1 and atorvastatin (10 mg/day) for another 12 weeks in period 2, whereas patients assigned to sequence 2 received atorvastatin (10 mg/day) for 12 weeks in period 1 and pitavastatin (2 mg/day) for another 12 weeks in period 2. Blood samples were collected at three visits (baseline, after 12 and 24 weeks). Results Lipid control was similar in both statins. The difference in glycated hemoglobin between pitavastatin and atorvastatin treatments was −0.18 (95% confidence interval −0.34 to −0.02; P = 0.03). Compared with atorvastatin, pitavastatin treatment significantly lowered the levels of glycoalbumin, fasting glucose and homeostasis model assessment of insulin resistance. Conclusions Our results showed that treatment with pitavastatin had a more favorable outcome on glycemic control in patients with type 2 diabetes compared with atorvastatin. This trial was registered with UMIN (no. 000003554).